The impact of post-activation potentiation on explosive vertical jump after intermittent time: a meta-analysis and systematic review - Li, Jiazhe; Soh, Kim Geok; Loh, Su Peng (Nature Research, 2024)
The optimal intermittent time for post-activation potentiation (PAP) training remains uncertain and contentious. This study employed a meta-analysis to systematically evaluate the effect of different intermittent times on PAP in relation to explosive vertical jump height. Relevant literature was sourced from CNKI, Wanfang, VIP, CBM, PubMed, Web of Science, and Google Scholar databases using keywords such as “postactivation potentiation,” “activation enhancement effect,” “PAP,” “explosive vertical jump,” “explosive vertical high jump,” and “intermittent time.” The search covered publications from the inception of each database until June 2024. Studies involving athletes (regardless of sport type) undergoing PAP training were included, with no restrictions on the methods used to induce PAP. Comparative analysis focused on the heights of countermovement jumps (CMJ) and peak ground reaction force (GRF) before and after interventions. The quality of the included studies was assessed using the Cochrane Risk of Bias Tool, and data were analyzed using RevMan5.3. The study included a total of 21 papers with 327 subjects, primarily using the squat as the method of PAP induction. The meta-analysis revealed that intermittent times of 4 min [MD = − 0.03, 95% CI: − 0.04 ~ − 0.01; Z = 2.71, P = 0.007] and 5–8 min [MD = − 0.03, 95% CI: − 0.04 ~ – 0.01; Z = 3.07, P = 0.002] significantly increased the height of explosive vertical CMJs. However, intermittent times of 1–3 min [MD = –0.00, 95% CI: − 0.01 ~ 0.01; Z = 0.38, P = 0.70] and 10–24 min [MD = − 0.01, 95% CI: − 0.02 ~ 0.00; Z = 1.43, P = 0.15] did not show significant effects on CMJ height. These findings indicate that 4-min and 5–8 min intervals significantly enhance CMJ height, while intervals shorter than 4 min or longer than 8 min do not have a significant impact.